Beyond parents and guardians: Mapping and mobilizing the "significant others" in early childhood care and development in the Philippines - Paul Gideon D. Lasco; Jhaki A. Mendoza (Philippine Institute for Development Studies (PIDS), 2025)
ECCD discourse, policy, and research have understandably focused on parents: their roles, knowledge, practices, and lived experiences. However, it truly 'takes a village' to raise a child, perhaps particularly so in a very intergenerational, communal society like the Philippines where both of the past (e.g. cultural history) and the future (e.g. demographic shifts) point to the greater involvement of various 'significant others' in the pag-aalaga (i.e. care or nurturing) of children. This report examines how Filipino parents approach early childhood development, emphasizing the central role of various actors-parents, siblings, grandparents, domestic helpers (yayas, kasambahays), and community members (e.g., barangay health workers)-in shaping children's early development. Inspired and informed by 17 key informant interviews and a review of the social sciences literature, we map the different participants in ECCD and propose possible ways to leverage them toward better child health and education outcomes.
Keywords: 330; early childhood care and development; childrearing; parenting experiences; caregiving network; qualitative research